2023
DOI: 10.1038/s41467-023-38626-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning how network structure shapes decision-making for bio-inspired computing

Abstract: To better understand how network structure shapes intelligent behavior, we developed a learning algorithm that we used to build personalized brain network models for 650 Human Connectome Project participants. We found that participants with higher intelligence scores took more time to solve difficult problems, and that slower solvers had higher average functional connectivity. With simulations we identified a mechanistic link between functional connectivity, intelligence, processing speed and brain synchrony f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 84 publications
1
9
1
Order By: Relevance
“…Our results align with a recent study by Schirner et al ( 2023 ), which found that participants in the Human Connectome Project who had higher Penn Matrix Reasoning scores were those who took longer on hard questions. They linked the differential time allocation to easy and hard problems to measures of functional connectivity, finding that slower solvers had higher resting state connectivity.…”
Section: Discussionsupporting
confidence: 92%
“…Our results align with a recent study by Schirner et al ( 2023 ), which found that participants in the Human Connectome Project who had higher Penn Matrix Reasoning scores were those who took longer on hard questions. They linked the differential time allocation to easy and hard problems to measures of functional connectivity, finding that slower solvers had higher resting state connectivity.…”
Section: Discussionsupporting
confidence: 92%
“…The simulation of FC via noise integration is easier to compare with previous work as it has been extensively simulated and studied (8). Our results do not have the highest correlation in comparison to other methods, as some recent studies have correlations utilizing higher parcellations above 0.9 compared to our average correlation of about 0.7 (32). However, as illustrated in Supplemental Figure 9, the FC metric is the least specific in analyzing dynamical systems and is rather uninformative and we believe that the prediction of the actual timeseries are much more informative of the performance of the model.…”
Section: Discussioncontrasting
confidence: 88%
“…Compared to other estimates of behavioral correlates using HCP WM data, our results are quite promising as getting r-squared beyond 0.4 seems challenging (37). Another recent paper that uses network modeling to make inferences about WM using HCP data, but instead looks at average RT metrics across WM trials rather than predicting them on a per trail basis (32). Our results compared to this paper are contradictory, as it claims that there are fast and slow learners and proceeds to separate the HCP population into 5 distinct groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimension 2 loadings, interpreted as processing speed, were high for tests considering reaction time. Our findings may relate to the accuracy-speed relationship described by Schirner et al (2023) using alternative estimates of g and processing speed, where accuracy is linked to high FC strength (thus FC stability), and speed with low FC strength (thus FC variability). Accuracy is facilitated by a mode of cognition where high synchrony yields longer decision -making windows for information integration, whereas speed is facilitated by a mode where low synchrony grants shorter windows for rapid decision-making.…”
Section: Discussionmentioning
confidence: 67%